Exploring Bad News in a Clinical Setting - Amanda Puspanditaning Sejati; Sifa Rini Handayani; Dedah Ningrum; Emi Lindayani (Journal of English Language Studies, 2023)
Effective communication in clinical interaction is an important issue because the message must be received appropriately by the patient to increase the patient’s health quality. It could become more complex when the communication occurred in sensitive contexts such as the delivery of bad news related to the patient's health condition. Studies on the genre of delivering bad news by doctors and the linguistic features used that are realized in medical-themed movies have not been widely studied. Therefore, this study aims to describe the generic structure and linguistic features used by doctors to convey bad news in The Resident movie. This study used content analysis as research design and Systemic Functional Linguistics (SFL) as tool of analysis. The data used was the doctors’ speeches when delivering bad news in The Resident Season 5. In addition, this study employed a genre analysis of the Systemic Functional Linguistics point of view to analyze the data. The results showed that the generic structure of telling bad news in a clinical context is *(Preparing Patient)^*<(Explaining Reason)>^*<Telling Bad News>^*<(Reinforcing Patient)>^*<(Explaining Procedure)>^*(Offering Choices). In addition, several linguistic features are used by doctors to convey bad news including the use of present and future tenses, conditional sentences, lexical cohesion markers 'but', sentences, and negative lexical markers 'not'. The findings in this study can be used to develop English for Specific Purposes course material.